Production and partitioning of dry matter in eddoe (Colocasia esculenta var. antioquorum) - Waaijenberg, H.; Aguilar, E. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Ilus. Fig. 3 tab. 11 ref. Sum. (En). También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 68